KONSUMSI BUAH NANAS TERHADAP KESEHATAN GIGI DAN MULUT - santoso, simon; setiawaty ningsih, neny; halimah, halimah; heru, jojok; herlina, rita (JURNAL TERAPIS GIGI DAN MULUT, 2022)
Pineapple (Ananas comosus L. Merr) is a fruit that contains water and fiber as well as bromelin enzyme as an antibacterial. Dental and oral health is part of overall body health and cannot be separated from general body health. Based on this background, this study aims to find out more about the benefits of pineapple fruit for oral health. This study uses the study literature review method, namely the method of collecting and tracing bibliographical data, textbooks, journals, scientific articles, and literature reviews related to the discussion to be studied. The results showed pineapple (Ananas comosus L. Merr).Some of these ingredients have been known to inhibit bacterial growth through disruption of protein biosynthesis, nucleic acid metabolism, and inhibition of enzyme activity such as glucosyltransferases. These materials can also inhibit bacteria from producing acid, synthesizing exopolysaccharides and bacterial attachment. Based on the research results, the content of pineapple fruit solution (Ananas comosus L. Merr) contains citric acid and phenolic compounds which are antibacterial.Pineapple consumption can reduce dental plaque, Streptococcus sp bacteria, and increase salivary pH.